THE UTILITY OF OIL SHOWS IN THE HYDROCARBON EXPLORATION OF WESTERN GREECE - Rigakis, N.; Nikolaou, K.; Marnelis, F.; Pakos, Th. (Bulletin of the Geological Society of Greece, 2007)
A great number of oil shows are known in Western Greece, mainly in the Ionian zone, but also in the Preapulian and Gavrovo zones. Most of the wells drilled in the area have also identified oil shows. The systematic study of these oil shows provides a useful tool for the hydrocarbon exploration of this area. First of all the presence of oil shows indicates that oil generation and migration have certainly taken place. Furthermore by their study the petroleum systems of western Greece can be confirmed. Oil shows were analyzed using chemical methods. Because most surface oil shows are biodegraded, the study was mainly based on carbon isotopes measurements and on characteristic biomarker ratios. The oil shows can be classified into five main groups, based on their different compositions, while two of them are separated in two subgroups. This differentiation proves the presence of different source rock horizons, which have generated these oils.